2011
DOI: 10.1007/s13313-011-0055-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil organic amendments on suppression of the burrowing nematode, Radopholus similis, on the growth of bananas

Abstract: Radopholus similis is a major constraint to banana production in Australia and growers have relied on nematicides to manage production losses. The use of organic amendments is one method that may reduce the need for nematicides, but there is limited knowledge of the influence of organic amendments on endo-migratory nematodes, such as R. similis. Nine different amendments, namely, mill mud, mill ash, biosolids, municipal waste compost, banana residue, grass hay, legume hay, molasses and calcium silicate were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…In the banana soil, most of 11 plantparasitic nematode species identified in our study occur commonly in the soil, together with the dominant Radopholus similis (35,36).…”
Section: Pottingmentioning
confidence: 69%
“…In the banana soil, most of 11 plantparasitic nematode species identified in our study occur commonly in the soil, together with the dominant Radopholus similis (35,36).…”
Section: Pottingmentioning
confidence: 69%
“…The rhizosphere microbial diversity will undergo substantial modification following organic mulching, which will depend on the type of OM, the climate, soil type, etc. [140]. The possible negative impact by P. goodeyi on banana in Rwanda, for instance, was likely masked by the fact that nematode populations were positively correlated with high plant density and/or mulching practices, which reduced root necrosis and led to relatively high plant vigor, irrespective of soil type [141].…”
Section: Effects Of Banana Cropping Systems On Nematodesmentioning
confidence: 99%
“…This is likely due to multiple reasons, including the modification of the rhizosphere soil microbial community, which becomes richer and more populated with mulching. Studies on plantain in West Africa have consistently demonstrated the improved productivity and longevity of plantations infected with nematodes following mulching, irrespective of the type of mulch [137,[142][143][144], and similarly elsewhere on other banana types [140,145,146]. The regular application of relatively small amounts of fresh Tithonia diversifolia leaf material to plantain heavily affected by nematodes in Nigeria demonstrated great beneficial effects on crop performance [147].…”
Section: Effects Of Banana Cropping Systems On Nematodesmentioning
confidence: 99%
“…Among the available organic amendments, molasses, a byproduct from the sugar beet or sugarcane industry, has been assessed alone or combined with urea against plant-parasitic nematodes, including Meloidogyne spp. [18][19][20][21][22][23], with variable results. Molasses has also been used as carbon source combined with composted poultry litter in anaerobic soil disinfestation [24].…”
Section: Introductionmentioning
confidence: 99%